Pengembangan Bahan Ajar PAI Berbasis Sistem - Radinal Mukhtar Harahap; Ahmad Zaki Azzahiri; Rasyidin Rasyidin (Institut Nurul Islam, 2026)
This article examines the development of Islamic Education (PAI) learning materials through a systemic approach that views education as an interconnected and interdependent process. Education is conceptualized as a system composed of curriculum, learning objectives, learners’ characteristics, instructional strategies, media, and assessment—all of which operate in an integrated manner. Within this framework, learning materials are not merely content to be delivered but pedagogical instruments that connect Islamic educational goals with classroom practices. The article outlines the systemic foundations of PAI material development, design principles aligned with curriculum standards, and structural components of learning materials that support cognitive, affective, and psychomotor integration. It further discusses various types and formats of PAI materials suitable for basic and secondary education, including printed materials, visual media, digital resources, and experiential learning tools. By embedding Islamic values, contextual relevance, and meaningful activities, systemic-based learning materials enhance the effectiveness of instruction and contribute to sustainable character formation. This article highlights the essential role of teachers in designing purposeful, flexible, and adaptive learning materials that respond to students’ needs and the challenges of contemporary education.